Morinda citrifolia (Noni) Fruit Juice Reduces Inflammatory Cytokines Expression and Contributes to the Maintenance of Intestinal Mucosal Integrity in DSS Experimental Colitis - Beatriz Coutinho de Sousa; Juliana Reis Machado; Marcos Vinicius da Silva; Thiago Alvares da Costa; Javier Emilio Lazo-Chica; Thatiane do Prado Degasperi; Virmondes Rodrigues Junior; Helioswilton Sales-Campos; Elizabeth Uber Bucek; Carlo José Freire Oliveira (Hindawi Limited, 2017)
Morinda citrifolia L. (noni) has been shown to treat different disorders. However, data concerning its role in the treatment of intestinal inflammation still require clarification. In the current study, we investigated the effects of noni fruit juice (NFJ) in the treatment of C57BL/6 mice, which were continuously exposed to dextran sulfate sodium (DSS) for 9 consecutive days. NFJ consumption had no impact on the reduction of the clinical signs of the disease or on weight loss. Nonetheless, when a dilution of 1 : 10 was used, the intestinal architecture of the mice was preserved, accompanied by a reduction in the inflammatory infiltrate. Regardless of the concentration of NFJ, a decrease in both the activity of myeloperoxidase and the key inflammatory cytokines, TNF-α and IFN-γ, was also observed in the intestine. Furthermore, when NFJ was diluted 1 : 10 and 1 : 100, a reduction in the production of nitric oxide and IL-17 was detected in gut homogenates. Overall, the treatment with NFJ was effective in different aspects associated with disease progression and worsening. These results may point to noni fruit as an important source of anti-inflammatory molecules with a great potential to inhibit the progression of inflammatory diseases, such as inflammatory bowel disease.